1987
DOI: 10.3758/bf03327291
|View full text |Cite
|
Sign up to set email alerts
|

Memory-enhancing effect of posttraining epinephrine is not blocked by dexamethasone

Abstract: There is extensive evidence that stress-related honnones administered shortly before or after training on a variety oftasks can influence retention (de Wied, 1984;McGaugh, 1983). Such evidence suggests that hormones released by learning experiences may serve as endogenous modulators of memory storage (Gold & McGaugh, 1984).Recently, Tilders, Berkenbosch, Vermes, Linton, & Smelik (1985) reported that a number of honnones, in addition to corticotrophin releasing factor (CRF) , induce the release of adrenocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although these data clearly indicate that ACTH is important in mediating recovery from experimentally induced amnesia, a recent report suggests that this hormone may not be as critical with respect to memory enhancement. McGaugh et al (1987) have reported that epinephrine-induced memory enhancement in rats was not related to a congruency of ACTH at training and testing. This finding suggests that drug-induced memory enhancement may be different from recovery from amnesia and, as such, may be mediated by different psychobiological processes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although these data clearly indicate that ACTH is important in mediating recovery from experimentally induced amnesia, a recent report suggests that this hormone may not be as critical with respect to memory enhancement. McGaugh et al (1987) have reported that epinephrine-induced memory enhancement in rats was not related to a congruency of ACTH at training and testing. This finding suggests that drug-induced memory enhancement may be different from recovery from amnesia and, as such, may be mediated by different psychobiological processes.…”
Section: Discussionmentioning
confidence: 98%
“…Data from control groups discounted alternative interpretations focusing on stress-induced performance artifacts. For example, dexamethasone administration before training or testing did not interfere with the animal's ability to learn or to perform the passive avoidance task, respectively–a conclusion previously made by other investigators (e.g., Beatty et at., 1970; Kasper-Pandi et at., 1970; McGaugh, Bennett, Liang, Juler, & Tam, 1987). Although plasma measures of ACTH after dexamethasone treatment were not available, indirect evidence of dexa-methasone's effect is seen in reduced body weights.…”
Section: Discussionmentioning
confidence: 99%